Micro-hardness of Acrylic Resin utilized for Provisional Crowns: Effect of different polymerization techniques and pH-Cycling - César Augusto Zanlorenzi Nicodemo; Carlos Eduardo Edwards Rezende; Rafael Tobias Moretti-Neto; José Henrique Rubo (Brazilian Dental Science)
Objective: This study aimed at evaluating the micro-hardness of an acrylic resin used for provisional crowns. Materials and methods: Five different processing techniques (direct and indirect) were assessed: (I) auto polymerizing resin in sandy stage; (II) auto polymerizing resin in plastic stage; (III) bead-brush technique; (IV) auto polymerizing resin under pressure; (V) heat-cured acrylic resin under pressure. Five specimens were made for each test group. For the initial micro-hardness test, the specimens were immersed in deionized water for 48 hours. For the analysis of the final micro-hardness, the specimens were subjected to pH-cycling to simulate the changes in the pH level which occur in the oral cavity. Results: Tests revealed that the micro-hardness was decreased after the pH-cycling. However, no statistical difference was found among the different types of acrylic resin polymerization techniques. Conclusion: It was concluded that the micro-hardness is not directly related to the polymerization technique for making provisional crowns.